TRIM62 From Chicken as a Negative Regulator of Reticuloendotheliosis Virus Replication - Li, Ling; Niu, Dongyan; Yang, Jie; Bi, Jianmin; Zhang, Lingjuan; Cheng, Ziqiang; Wang, Guihua (Frontiers in Veterinary Science, 2020)
Emerging evidence suggests that the tripartite motif containing 62 (TRIM62), a member of the TRIM family, plays an important role in antiviral processes. The objective of the study was to explore role of TRIM62 in reticuloendotheliosis virus (REV) infection and its potential molecular mechanism. We first demonstrated that the REV infection affected the TRIM62 expression first upregulated and then downregulated in CEF cells. Next, we evaluated the effect of TRIM62 on viral replication. Overexpression of TRIM62 decreased REV replication. On the contrary, silencing of endogenously expressed TRIM62 increased viral replication. Then, to explore the necessity of domains in TRIM62’s negative regulation on viral replication, we transfected CEF cells with TRIM62 domain deletion mutants. Deletion domain reduced TRIM62 expression and partially abolished TRIM62’s antiviral activity. The effect of SPRY domain deletion was the most and that of coiled-coil was the least. Further, we identified 18 proteins that coimmunoprecipitated interacted with TRIM62 by immunocoprecipitation and mass spectrometry analysis. Strikingly, among which both Ras-related protein Rab-5b (RAB5B) and Arp2/3 complex 34 kDa subunit (ARPC2) were involved in actin cytoskeletal pathway. Altogether, these results strongly suggest that chicken TRIM62 provides host defense against viral infection, and all domains are required for its action. RAB5B and ARPC2 maybe played important roles in its negative regulation processes.